Effect of Irrigation Depth and Nitrogen Fertilizer Rates on Pepper (Capsicum annum L.) Yield and Water Use Efficiency in Tselemty District, Tigray, Ethiopia - Gebreigziabher, Ekubay Tesfay; Gebremedhin, Teferi; Fissha, Netsaner (International Journal on Food, Agriculture and Natural Resources, 2024)
Optimizing agricultural crop production involves utilizing proper irrigation and fertilization techniques. A two-year experiment conducted in the Tselemty district during the off seasons of 2019 and 2020 aimed to assess the impact of varying irrigation levels and nitrogen fertilizer application rates on the growth, yield, and crop water productivity of pepper. The study included three irrigation levels (75%, 100%, and 125% of the required irrigation) and three nitrogen fertilizer application rates (75%, 100%, and 125% of the recommended amount). Analysis of the results using Gen-Stat software revealed that most pepper yield attributes were not significantly affected by the different irrigation and fertilizer levels. However, the marketable yield showed significant variation based on the combined application rates. The research indicates that, under ideal circumstances, the optimal approach for pepper growers is a combination of meeting 100% of the irrigation requirement and applying 100% of the recommended nitrogen fertilizer rate. Nevertheless, in scenarios where water resources are limited and fertilizer expenses are high, a reduced irrigation level of 75% of the requirement coupled with 75% of the recommended nitrogen fertilizer rate could be a viable alternative that does not lead to a substantial decrease in yield.